A renda básica familiar e a justiça social : caminhos para o desenvolvimento como liberdade através da transferência de renda à luz da Constituição Econômica de 1988 - Lessa, Raul Messias (2023)
The social inequality and food insecurity are perennial in brazilian society, capillarizing our history from colonization to the present day. After a decade of reducing food insecuritys rates, through affirmative state benefits income transfer programs, such as the Family Aid Program, Brazil has once again suffered from the return of hunger in Brazilian society, affecting approximately 60% of households in 2021, at most, in regions such as the North and Northeast, where the rates reach 71% and 68%, respectively, as released by the Brazilian Institute of Geography and Statistics (IBGE) in 2022. Meanwhile, the Brazilian legal system has a legal framework that determines the protection of the most vulnerable. Purpose of the Federal Constitution, the eradication of poverty and reduction of inequality depend on public power actions actions that promote material equality so that everyone has the same conditions to develop, and the promotion of material freedom, characterized by the exercise of individual autonomy. To follow this path, the Law nº 10.835/2004 was published, wich instituted the basic income of citizens, having not been duly regulated by Executive Decree. In this regard, the STF determined, in Injunction Warrant nº 7.300, that the federal government implement the payment of the citizenship basic income to all brazilians in situation of poverty and extreme poverty. However, in December 2021, Constitucional Amendment nº 114/2021 was enacted, which embodied in the constitucional text the basic family income for brazilians in a situation of social vulnerability. Otherwise, backed by the advance of neoliberal policies, the derived constituent reformed the original constitucional text more than a hundred times in its budgetary and fiscal provisions. The aim of this dissertation is to shed light on Constitutional Amendment nº 95/2016, which imposed a spending ceiling, making it impossible to promote public policies and increase income transfer programs, especially in the context of socioeconomic chaos experienced by virtue of the Covid-19 pandemic. Therefore, the following research problem is presented: is it possible to implement a universal basic family income that guarantees a dignified existence for the most vulnerable, reducing social inequality and food insecurity, as a path to freedom through development, in the light of a Social status? As a hypothesis, it is assumed that state action is fundamental for the realization of social rights, and the state must implement a universal basic income that guarantees subsistence, development, human dignity, freedom, equality and the promotion of social justice. Without disregarding fiscal responsibility, which must be combined with social responsibility, it is suggested, as an alternative hypothesis, the implementation of a basic family income under the terms of the Constitution: not universal, but aimed at the vulnerable. The financing of the basic income will take place through a new fiscal regime and application of the theory of optimal taxation. Therefore, the welfare state – a historic achievement of humanity and reflected in the Brazilian Economic Constitution – must be maintained based on the principle of solidarity and protection of the most vulnerable layers, with the minimum income program being a viable and sustainable path for the generating a virtuous cycle of economic growth, development and freedom.